2018
DOI: 10.1016/j.neuroimage.2018.04.056
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic functional connectivity markers of objective trait mindfulness

Abstract: While mindfulness is commonly viewed as a skill to be cultivated through practice, untrained individuals can also vary widely in dispositional mindfulness. Prior research has identified static neural connectivity correlates of this trait. Here, we use dynamic functional connectivity (DFC) analysis of resting-state fMRI to study time-varying connectivity patterns associated with naturally varying and objectively measured trait mindfulness. Participants were selected from the top and bottom tertiles of performer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
55
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

2
7

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 65 publications
6
55
1
1
Order By: Relevance
“…In the centroid correlation matrix ( Supplementary Figure 1a), we observed that there was not a clear one-to-one statistical correspondence between the states obtained in Lim et al 2018, and those found in this experiment. As a further analysis to determine the distinctness of the connectivity states in our current dataset, we performed dynamic functional connectivity analysis using the pipeline described in this paper on a larger dataset of N = 173 resting-state of fMRI scans collected across our research center.…”
Section: Reproducibility Of Dynamic Connectivity Statescontrasting
confidence: 74%
See 1 more Smart Citation
“…In the centroid correlation matrix ( Supplementary Figure 1a), we observed that there was not a clear one-to-one statistical correspondence between the states obtained in Lim et al 2018, and those found in this experiment. As a further analysis to determine the distinctness of the connectivity states in our current dataset, we performed dynamic functional connectivity analysis using the pipeline described in this paper on a larger dataset of N = 173 resting-state of fMRI scans collected across our research center.…”
Section: Reproducibility Of Dynamic Connectivity Statescontrasting
confidence: 74%
“…While results from these experiments are mixed, there is some agreement that mindfulness is associated with increased connectivity within the default mode network, and in particular between the posterior cingulate cortex and ventromedial prefrontal cortex, greater anti-correlations between the default mode network and attentional/control areas, and an increase in connectivity between regions of the ventral attentional network (particularly the insula) and executive control areas (see Mooneyham et al, 2016 for a review). Furthermore, studies have also found variation in dynamic connectivity that corresponds with trait mindfulness (Mooneyham et al, 2017;Lim et al, 2018;Marusak et al, 2018). In a recent study, we identified a mindfulness-related connectivity state (which we named the "taskready" state) that recapitulates some of the most robust features of findings from static connectivity; high levels of intra-network connectivity in the default mode network and ventral attention network, and strong anti-correlations between these same networks .…”
Section: Introductionmentioning
confidence: 89%
“…In addition, the increase of metastability in meditators during resting-state is congruent with the increase of the temporal complexity of oscillations during rest in meditators observed in the previously mentioned study [34]. Moreover, studies applying 140 a dynamical functional connectivity approach found that individuals with high trait mindfulness, transitioned more frequently between brain states at rest [13,36].…”
supporting
confidence: 80%
“…Lim et al (2018); r s-TRS = 0.89, r s-LAS = 0.90, r s-HAS = 0.91) and moderately correlated with centroids obtained using the sliding-window approach): r s-TRS = 0.77, r s-LAS = 0.60, r s-HAS = 0.74). The characteristics of the named states are as follows: A) The LAS features lower within-network correlations and relatively small anticorrelations between task-positive networks (dorsal attention network (DAN), ventral attention/salience network (VAN), executive control network (ECN)) and the default-mode network (DMN).…”
mentioning
confidence: 74%